Pengaruh tentang PPG, PLP, persepsi kesejahteraan guru terhadap minat mengikuti PPG dengan mediasi motivasi menjadi guru - Intan Wahyu Utami; Jarot Tri Bowo Santoso (Jurnal Pendidikan Ekonomi (JUPE), 2026)
Students’ interest in participating in the Teacher Professional Education Program (PPG) represents a critical issue in the preparation of future educators, while studies examining the mediating role of motivation to become a teacher remain limited. This study aims to analyze the effects of perceptions of PPG, the School Field Introduction Program (PLP), and perceptions of teachers’ welfare on students’ interest in enrolling in PPG, with motivation to become a teacher serving as a mediating variable. A quantitative approach was employed, involving students of Economics Education at Universitas Negeri Semarang, and the data were analyzed using PLS-SEM with SmartPLS. The findings indicate that perceptions of PPG and motivation to become a teacher have positive effects on students’ interest in PPG, with motivation emerging as the most influential factor. Additionally, perceptions of teachers’ welfare exert an indirect effect through motivation, whereas PLP experience does not show a significant influence. These findings highlight the importance of strengthening positive perceptions of PPG and enhancing motivation to become a teacher in order to increase students’ interest in participating in the program.